Miro1 Impairment in a Parkinson’s At-Risk Cohort - Nguyen, David; Bharat, Vinita; Conradson, Devon M.; Nandakishore, Pawan; Wang, Xinnan (Frontiers in Molecular Neuroscience, 2021)
There is a lack of reliable molecular markers for Parkinson’s disease (PD) patients and at-risk individuals. The detection of the pre-symptomatic population of PD will empower more effective clinical intervention to delay or prevent disease onset. We have previously found that the mitochondrial protein Miro1 is resistant to mitochondrial depolarization-induced degradation in fibroblasts from a large number of PD patients and several at-risk individuals. Therefore, Miro1 has the potential to molecularly label PD populations. In order to determine whether Miro1 could serve as a molecular marker for the risk of PD, here we examine the Miro1 response to mitochondrial depolarization by biochemical approaches in induced pluripotent stem cells from a cohort of at-risk individuals. Our results show that the Miro1 phenotype is significantly associated with PD risk. We propose that Miro1 is a promising molecular marker for detecting both PD and at-risk populations. Tracking this Miro1 marker could aid in diagnosis and Miro1-based drug discoveries.